2021
DOI: 10.1101/2021.04.09.439133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shorter effective lifespan in laboratory populations ofD. melanogastermight reduce sexual selection

Abstract: The role of sexual selection in mediating levels of sexual conflict has been demonstrated in a number of experimental evolution studies on Drosophila sp. where the level of competition among males for fertilization success was under direct selection. Here we report that selection for a short development time and early age at reproduction can lead to inadvertent changes in levels of sexual selection in D. melanogaster populations, affecting reproductive competition experienced by males. We demonstrate that fast… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…The copyright holder for this preprint this version posted November 2, 2021. ; https://doi.org/10. 1101/2021 In an independent investigation on a similar set of experimentally evolved populations, (Mital et al 2021a;Mital et al 2021b) found that the intensity of sexual selection and the degree of sexual antagonism to be lower in populations selected for faster development and very early reproduction. The parallel between our results and those of (Mital et al 2021a;Mital et al 2021b) is somewhat expected, and is a robust proof in support of our theory.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted November 2, 2021. ; https://doi.org/10. 1101/2021 In an independent investigation on a similar set of experimentally evolved populations, (Mital et al 2021a;Mital et al 2021b) found that the intensity of sexual selection and the degree of sexual antagonism to be lower in populations selected for faster development and very early reproduction. The parallel between our results and those of (Mital et al 2021a;Mital et al 2021b) is somewhat expected, and is a robust proof in support of our theory.…”
Section: Discussionmentioning
confidence: 99%